Machinability study of glass fibre-reinforced polymer composites during end milling - Azwan Iskandar, Azmi; Lin, Richard J.T.; Bhattacharyya, Debes (Springer-Verlag London., 2013)
Link to publisher's homepage at http://link.springer.com/